Biogeochemical cycling and environmental footprints of peatland-derived organic carbon in the coastal ocean in Southeast Asia - Zhou, Yongli (Nanyang Technological University, 2021)
Each year, 0.2–0.25 Pg C of dissolved organic carbon (DOC) is delivered from land to ocean by riverine transport. This riverine flux of terrigenous DOC alone is sufficient to support the turnover of the entire oceanic DOC pool, which means that terrigenous DOC can in theory dominate the DOC pool in the ocean. However, data on the chemical composition of DOC in the ocean have generally been interpreted as showing that only a small fraction (<25%) of the oceanic DOC pool is of terrestrial origin. This discrepancy opens an important question for our understanding of the global carbon cycle: where has the “missing” terrigenous DOC gone?